Studying the synoptic gospels Origin and interpretation - Stein, Robert H. (Grand Rapids Baker Academic, 2001)
Stein examines in-depth the literary relationship of the Synoptic Gospels, the preliterary history of the gospel traditions, and the inscripturation of the gospel traditions. Previously published as The Synoptic Problem, this thoroughly updated edition ha
Keywords: Synoptic problem. Synoptische evangeliën. Vormkritiek